Identifikasi Senyawa Metabolit Sekunder Sebagai Senyawa Kompleks pada Tanaman Tradisional - Safitri Rahmat; Nadila Nadila; Deswita Deswita; Sasmita Putri Hairani; Yeyen Yeyen; Ensu Ensu (Polygon : Jurnal Ilmu Komputer dan Ilmu Pengetahuan Alam, 2025)
Various recent studies have shown that natural active compounds contained in traditional and fermented plants play a crucial role in supporting human health. These compounds include flavonoids, polyphenols, tannins, saponins, alkaloids, organic acids, probiotics, and other phenolic compounds. Detection of these compounds is usually carried out through specific chemical reactions that allow researchers to more precisely identify the bioactive components. Their biological activities are diverse, including antioxidant, antibacterial, anti-inflammatory, and antimicrobial properties, which work to protect the body from cell damage and infection. Natural compounds are considered promising agents for disease prevention and health promotion due to their broad biological activities. The fermentation process has been shown to increase the content of bioactive compounds while lowering the pH of the medium, creating conditions unfavorable for the growth of pathogenic bacteria. Furthermore, probiotics that develop during fermentation play a role in maintaining the balance of the gut microbiota, strengthening the immune system, and improving digestive health. Fermented products are widely recognized as functional foods because they contain beneficial probiotics and enhanced bioactive compounds. These naturally derived products, rich in secondary metabolites, have also been shown to have significant physiological effects, such as lowering cholesterol levels, controlling blood sugar, and maintaining stable blood pressure. This makes natural ingredients and fermented products not only sources of nutrition but also have great potential for development as functional foods and traditional herbal medicines. This highlights the importance of integrating traditional knowledge with modern scientific approaches in developing functional foods and herbal medicines. Therefore, research on natural bioactive compounds and the role of fermentation in enhancing their effectiveness is highly relevant to supporting sustainable public health.